Origins and evolution of the copyright system in England and the U.S. - Thomas Gergen (Journal on European History of Law, 2011)
Based on the two different systems of copyright protection, namely the droit d'auteur and copyright, this article examines the origins and developments of copyright in England and the United States of America up to the present day. Protection began in the 16th century in England with the granting of rights to the 'Company of Stationers' (booksellers' guild), which was allowed to maintain a register of books. In 1709/10, the first copyright law in England, the 'Statute of Anne,' followed, and the first in the USA was the 'Copyright Act' of 1790. In 1998, the American legislature extended the protection period for Mickey Mouse by 20 years with a specific law; the period thus expires in 2018.